Māhtāb-i Shām-i Sharq : Guzāra wa guzīna-yi andisha shinasī-yi Iqbāl - Sākit, Muḥammad Ḥusayn, (Miras Maktoob, ISBN: 9789004365452., 2019)
A lawyer by profession and an Urdu and Persian poet by vocation, Muḥammad Iqbāl (1877-1938) is the spiritual father of Pakistan. Born in Sialkot, he received his pre-college education in his hometown, after which he went to study in Lahore. In 1905, after several years of teaching (Arabic, English and philosophy) in Lahore, he travelled to Cambridge to study philosophy and law. Two years later, he went to Heidelberg, where he received his PhD in 1907 with a thesis entitled The Development of Metaphysics in Persia . He then returned to Lahore, working as a lawyer for most of his life. From around 1910 onwards, Iqbāl's poetry and prose works show an increased commitment to the cause of Islam and its political and societal ramifications, culminating in his idea of an Islamic state in northern India, the future Pakistan. The articles published in this volume all highlight different aspects of Iqbāl's life, work, and thought.